(untitled) (Research, Society and Development, 2020)
The need for communication is an essential tool for the socio-cultural development of human beings. The inclusion of people with some type of disability is necessary and fair in the face of the society in which it is inserted, taking into account their particularities. And, for people with hearing loss it would be no different, the Brazilian Sign Language has become a precious and indispensable tool for effective communication between the interlocutors involved. However, many difficulties are still encountered by these people, especially when it comes to effective care related to when talking about health. It aims to investigate the knowledge of Libras by health professionals and their perception of the care of deaf patients. Having as target population health professionals members of UBS Leopoldo Lins, located in the city of Tamandaré-PE. Being applied through a structured questionnaire, referring to the knowledge of pounds, in a favorable environment, the data collected and later this questionnaire will be analyzed and demonstrated through quantitative description. It was possible to identify a varied sample in relation to the academic profile and professional performance. In analyzing the results of the questionnaires, it was identified that of the 6 professionals interviewed, only 1 (16.6%) reported having partial knowledge of the language. It can be concluded that many professionals claim not to have this knowledge, which makes it difficult to assist the patient, who is often not understood by the professional and the professionals who are also unable to meet all their needs effectively.